The 2023 Groningen conference: The Netherlands as a symbolic location for the conference of the International Association for the Psychology of Religion - Grzymała-Moszczyńska, Halina (Archive for the psychology of religion, 2024)
The historical importance of The Netherlands for the International Association for the Psychology of Religion (IAPR) is connected to the beginning of the current form IAPR. Four years pause between the Gdańsk conference (2019) and the Groningen conference (2023) due to the COVID-19 pandemic resulted in the online organization of the 2021 conference. The 2023 conference is being presented in a hybrid format in order to make use of the additional opportunities that the online format provides. Results of the members questionnaire are presented. They provide characteristics of the current composition of IAPR members because of their education, academic positions, and research interests.